Computer-Aided System Application Value for Assessing Hip Development - Jiang, Yaoxian; Yang, Guangyao; Liang, Yuan; Shi, Qin; Cui, Boqi; Chang, Xiaodan; Qiu, Zhaowen; Zhao, Xudong (Frontiers in Physiology, 2020)
ABSTRACT Purpose: A computer-aided system was used to semi-automatically measure Tönnis angle, Sharp angle, and center-edge (CE) angle using contours of the hip bones to establish an auxiliary measurement model for developmental screening or diagnosis of hip joint disorders. Methods: We retrospectively analyzed bilateral hip x-rays for 124 patients (41 men and 83 women aged 20 to 70 years) who presented at the affiliated Zhongshan Hospital of Dalian University in 2017 and 2018. All images were imported into a computer-aided detection system. After manually outlining hip bone contours, Tönnis angle, Sharp angle, and CE angle marker lines were automatically extracted and the angles were measured and recorded. An imaging physician also manually measured all angles and recorded hip development, and Pearson correlation coefficients were used to compare computer-aided system measurements with imaging physician measurements. Accuracy for different angles was calculated and the area under the receiver operating characteristic (AUROC) curve was used to represent the diagnostic efficiency of the computer-aided system. Results: For Tönnis angle, Sharp angle, and CE angle, correlation coefficients were 0.902, 0.887, and 0.902, respectively; the accuracies of the computer-aided detection system were 89.1%, 93.1%, and 82.3%; and the AUROC values were 0.940, 0.956, and 0.948. Conclusion: The measurements of Tönnis angle, Sharp angle, and CE angle using the semi-automatic system were highly correlated with the measurements of the imaging physician and can be used to assess hip joint development with high accuracy and diagnostic efficiency.